IMPLEMENTATION OF PROJECT BASED LEARNING (PJBL) BASED ON SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS (STEM) TO IMPROVE METACOGNITIVE THINKING ABILITY - Dian Fitri Mulyani; Syaiful Arif (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
Good learning is learning that combines approach with an appropriate learning model. The study is done to know the implementation of a learning model with a approach to students' metacognitive thinking ability. The study is conducted with a quantitative experiment, with qualitative descriptive data analysis techniques, using the distinctive quasi design using the research of one group pretest and posttest design. Data gathering instruments are a matter of written tests with multiple choisters, angkets and products design. Using a quantitative descriptive and statistic using a try-t two tailed and one tailed that previously had done normality and homogeneity tests.From research that has been done indicates levels for extr-36.25 so it can be concluded that the experimental class has a better methangnitiver thinking ability than the control class. Next up is the angket results with a solution for.30.75 so that it can be concluded that the experiment class has a better ability than the control class. The next test results with incentives for 16.19 so it can be concluded that experiment classes have better abilities than control class. The impact of research that has been done is as a footing and a referencing model selection with the right approach particularly in improving metacognitive thinking ability.